Provision of peer support at the intersection of homelessness and problem substance use services: a systematic 'state of the art' review - Joanna Astrid Miler; Hannah Carver; Rebecca Foster; Tessa Parkes (BMC, 2020)
Abstract Background Peer support refers to a process whereby individuals with lived experience of a particular phenomenon provide support to others by explicitly drawing on their personal experience. It has been adopted in a variety of service contexts including homelessness, substance use, mental and physical health. Those who experience homelessness have some of the most complex intersecting health and social challenges. This 'state of the art' review provides a systematic search and synthesis of literature examining use of peer support models within services for people impacted by homelessness and problem substance use. Methods A systematic search using six databases (CINAHL, SocINDEX, PsycINFO, MEDLINE, Scopus and Web of Knowledge) was conducted in August 2019 and identified 2248 papers published in English after the year 2000. After de-duplication and scanning titles/abstracts, 61 papers were deemed relevant. Three more papers (including one grey literature report) were identified via references, but two papers were later excluded due to relevance. The final 62 papers included studies conducted in five countries. A thematic analysis approach was used to compare and contrast the study findings and provide a synthesis of the main learning points. Results In recent years there has been a substantial increase in research examining the utility of peer support yet there is significant variation across this field. Alongside profiling the range of settings, aims, populations, and main outcomes of these studies, this paper also provides an overview of overarching themes: the overall effectiveness and impact of peer-staffed or peer-led interventions; and challenges commonly faced in these roles. Five themes relating to the challenges faced by peers were identified: vulnerability, authenticity, boundaries, stigma, and lack of recognition. Conclusions While our findings provide support for current efforts to involve individuals with lived experience in providing peer support to those experiencing concurrent problem substance use and homelessness, they also urge caution because of common pitfalls that can leave those providing the support vulnerable. We conclude that peers should be respected, valued, supported, and compensated for their work which is often profoundly challenging. Suggested guidelines for the implementation of peer involvement in research studies and service delivery are presented.